Effects of Feed Quality on Rumen Microbial Protein Synthesis in Sheep - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Microbial protein synthesis (MPS) in the rumen was estimated by the excretion of purine derivatives concentration (allantoin, uric acid, xanthine and hypoxanthine) in the urine of 16 rams of local breed, They were randomly allocated into 4 dietary regimes (as a treatment) i.e.: A (deficient in RDN)